Signal transducer and activator of transcription 3 signaling in tumor immune evasion - Zhang, Luying; Kuca, Kamil; You, Li; Zhao, Yingying; Musilek, Kamil; Nepovimova, Eugenie; Wu, Qinghua; Wu, Wenda; Adam, Vojtech (Pharmacology & therapeutics (Oxford), 2022)
The underlying mechanism of tumor immune evasion is a highly concerning subject for researchers. Increasing evidences reveal that the over-activated signal transducer and activator of transcription 3 (STAT3) is a crucial molecular hub in malignant tumors. STAT3 controls autophagy molecules that impair CTL-mediated tumor cell lysis, inhibiting natural killer cells and inducing apoptosis in T lymphocytes to create an immunosuppressive environment. STAT3 signaling regulates the expression of immune factors and recruits immunosuppressive cells to establish a tolerant tumor microenvironment (TME). STAT3 signaling regulates the expression of immune factors and recruits immunosuppressive cells to create an immunosuppressive environment. All this aid tumor cells in escaping from immune surveillance. In this review, we outlined the STAT3-mediated mechanisms involved in tumor immune evasion and their potential regulatory functions in the TME. We discussed the impact of STAT3 signaling on PD-L1, HIF-1α, exosome, lncRNA, and autophagy in the promotion of tumor immune evasion and highlighted the recent research on STAT3 signaling and tumor immune evasion that may assist in developing effective STAT3-targeted drugs for advancing immunotherapy.